International Experience of Organization and Activities of Forensic Expert Institutions - Chumak, V. V. (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The author of the article studies international experience of the organization and activities of forensic institutions on the example of such countries as Germany, France, the Netherlands, Czech Republic and the United Kingdom. The legislative features of the functioning of forensic institutions and the regulation of the legal status of experts are noted. It is determined that regardless of the departmental subordination of forensic institutions, their activities are based on international standards. The author has identified a scientific novelty, which consists in the further development of the provisions obtained by scientists and scholars on the organizational structure and practical activities of forensic institutions both in Ukraine and abroad, as well as the formulation of new conceptual provisions, conclusions and propositions for improving regulation of forensic activity in Ukraine. The author of the article proves that the organization and activities of forensic institutions in France are based on national and international law regulating the specifics of forensic examinations and the legal status of the expert. The author concludes that forensic activities in Germany, France, Spain, the Netherlands and the United Kingdom are carried out effectively, and its legal regulation takes place without violation of human rights and freedoms in compliance with international rules and standards. Their legislation, which addresses the organization and operation of forensic institutions, is aimed at respecting the rights and freedoms of a man and citizen, protection of the rights and interests of forensic experts. The author of the article defines that the implementation of international norms and standards of organization and activity of forensic institutions brings expert institutions to a new level of functioning. This makes it possible to create an effective mechanism for the management and operation of forensic institutions and experts, which will determine the high requirements for forensic examination, increase the professional level and efficiency of employees of expert institutions, which can meet the needs of modern justice.